The German linguistic validation of the Ureteral Stent Symptoms Questionnaire (USSQ) - Abt, Simon Dominik; Knoll, Thomas (World journal of urology, 2017)
Purpose: We developed and validated the German version of the Ureteral Stent Symptoms Questionnaire (USSQ) for male and female patients with indwelling ureteral stents. Methods; The German version of the USSQ was developed following a well-established multistep process. A total of 101 patients with indwelling ureteral stents completed the German USSQ as well as the validated questionnaires International Prostate Symptom Score (IPSS) or International Consultation on Incontinence Questionnaire (ICIQ) and the Short Form Health Survey (SF-36). Patients completed questionnaires at 1 and 2-4 weeks after stent insertion and 4 weeks after stent removal. Statistical analyses were performed to assess the psychometric properties of the questionnaire. Results: The German version of the USSQ showed good internal consistency (Cronbach’s α = .72-.88) and test-retest reliability [intraclass correlation coefficient (ICC) = .81-.92]. Inter-domain associations within the USSQ showed substantial correlations between different USSQ domains, indicating a high conceptual relationship of the domains. Except from urinary symptoms and general quality of life, German USSQ showed good convergent validity with the corresponding validated questionnaires. All USSQ domains showed significant sensitivity to change (p ≤ .001). Conclusion: The new German version of the USSQ proved to be a reliable and robust instrument for the evaluation of ureteral stent-associated morbidity for both male and female patients. It is expected to be a valid outcome measure in the future stent research.
Gesehen am 25.09.2018
Published online: 23 June 2016